THE INFLUENCE OF EMOTIONAL INTELLIGENCE, COMPETENCE AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF ENGLISH TEACHERS - Muhammad Khoirunnada (Kusuma Negara Business School, 2020)
This study was conducted to determine how much influence the Emotional Intelligence, Competence and Organizational Culture on the Performance of English Teachers in Private Junior High Schools in Cakung District, East Jakarta. both partially and simultaneously. The data collection method uses primary data from 75 respondents, but the data is complete and can be processed as many as 72 respondents. The data obtained were then processed using the multiple regression method with SPSS software version 23. The results showed that emotional intelligence both partially and simultaneously had a significant effect on Teacher Performance, Competency both partially and simultaneously had a significant effect on Teacher Performance, Organizational Culture both partially or simultaneously significant effect on Teacher Performance.